#TITLE_ALTERNATIVE# - WIDYA HESTY (NIM : 22412003); Pembimbing : Dr. Tri Wahyu Hadi, NURRY
An accurate and high resolution wind map are needed to reduce measurement cost and encourage wind energy industry in Indonesia. In this study, the state-of-the-art atmospheric mesoscale model WRF is used to map the wind resource at 50 m a.g.l. for the southern of West Java offshore. It is coupled with a nudging Four Dimension Data Assimiliation (FDDA) technique to ingest surface wind data Cross-Calibrated Multi-Platform (CCMP). Sensitivity test using six of the PBL parameterizations were compared. YSU PBL parameterization is selected to run throughout 2008 because it has the smallest error. Model results are verified against observational data from the anemometric mast at Sukabumi. Results show the FDDA technique can reduce RMSE and reproduce similar wind distribution patterns to the wind measurement data. Finally, three promising areas in on shore and offshore in south of West Java coastal waters for wind power generation are found out from power density and Annual Energy Production maps. The analysis is based on the potential availability of land and energy needs of the community showed Sukabumi more potential to be the location of wind energy development. However, the calculation of the cost of energy (CoE) shows that wind energy is less competitive compare to selling price of electricity by PLN, unless there is improvement in design of FiT for wind energy and disposal of the purchase price of electricity from renewable energy by PLN.